Extent of Trade between Nigeria and Partner ECOWAS Nations in Beverages and Tobacco - Akwaji, A. O.; Onogwu, G. O.; Dibah, J. B. (Kwaghe International Journal of Sciences and Technology, 2025)
This study investigates the dynamics of intra-regional trade in Beverages and Tobacco between Nigeria and other Economic Community of West African States (ECOWAS) member countries, with a focus on assessing trade volumes and terms of trade across the region. Specifically, it aims to (1) analyze the volume of exports and imports of Beverages and Tobacco among ECOWAS nations and (2) evaluate the evolving terms of trade between member states. Secondary data spanning multiple years were obtained from the TRAINS database and analyzed using descriptive statistical techniques. Results reveal that Nigeria has historically maintained a leading position in exports, peaking at 56.29% of regional trade in 2012, but declining to 23.04% by 2023, reflecting significant variability. Côte d’Ivoire and Senegal have emerged as key trade partners, while countries such as Burkina Faso and Ghana have shown increasing import dependence, indicating shifting regional trade dependencies. Furthermore, trends in terms of trade ratios, particularly Nigeria’s sharp rise to 276,786 in 2023 and Senegal’s peak of 50,547.1 in 2014, reflect robust export performance within the sector. The analysis underscores Nigeria and Côte d’Ivoire’s continued dominance but also highlights the rising participation of countries like Senegal, Togo, and Burkina Faso in the regional market. These findings suggest that intra-ECOWAS trade in Beverages and Tobacco is diversifying, offering new opportunities for economic cooperation. Policy interventions aimed at strengthening trade infrastructure, enhancing export capacity, and mitigating potential fiscal vulnerabilities are recommended to improve regional trade outcomes.